Family Business as Source of Municipality Development in the Czech Republic - Petra Rydvalová; Eva Karhanová Horynová; Magdalena Zbránková (Amfiteatru Economic Journal, 2016)
The article is focused on the family businesses in the Czech Republic. The main aim is to answer the question of whether the family entrepreneurship can be seen as an instrument of municipality development. First, the term family entrepreneurship based on foreign and domestic sources is defined. The sources are complemented by a legal viewpoint under the new Civil Code of the Czech Republic. Furthermore, a regional definition of a municipality and the country is specified. Then, a result of the research investigation focused on the link between the family entrepreneurship and economic development of communities is presented. Finally, the next steps of the team at the Faculty of Economics, Technical University of Liberec in the given area are unveiled. The novel idea is to use such a tool that allows its residents to find the meaning of life in the country and accept a certain level of inequality associated with it. Just at this moment, regional disparities can be removed and support for the development of rural areas can be successfully implemented. Also, family businesses can be a source of developing business environment, especially in small municipalities in rural areas.
Keywords: M10; M13; K20; 330; family business; entrepreneurship; business environment; municipality in a wider area; evaluating indicators; factors of development; balanced socio-economic development